Core decompression can still be an effective treatment in femoral head avascular necrosis - Tekin, Mustafa; Mirioğlu, Akif; Kundakçı, Buğra; Bağır, Melih; Biçer, Ömer Sunkar; Tan, İsmet (Scientific Reports in Medicine, 2025)
Objective: Core decompression is one of the femoral head sparing surgeries that is used in femoral head avascular necrosis. The efficacy of the treatment is inconsistent in the literature. We aimed to contribute to clarifying the controversies about the index treatment by publishing this retrospective paper. Methods: Functional and radiological data of 44 hips of 33 patients who were diagnosed with femoral head avascular necrosis and treated with core decompression were extracted from the hospital database. Presumed risk factors were determined as corticosteroid use, trauma, chemotherapy, sickle cell anemia, alcohol, and pregnancy. Twenty hips were treated with core decompression only, 24 hips were treated with core decompression and avascular bone grafting. All surgeries were performed with a standard technique which is described by Arlet and Ficat, and patients complied with standard follow-up protocol. Functional results were assessed with Harris hip score and radiological findings before and after the operations were evaluated by a single author. Results: The mean follow-up of patients was 89 (17-171) months. Patients had significant improvement in Harris hip score postoperatively regardless of the surgical technique. Sixteen hips (36.3%) underwent total hip arthroplasty (THA) during follow-up and there is no significant difference between treatment groups. Mean interval between the primary surgery and THA was 37.8 months. Conclusion: Core decompression can still be an effective treatment options at an early-stage avascular necrosis of the femoral head.